PERANCANGAN RUMAH SUSUN DI PONDOK KELAPA JAKARTA TIMUR DENGAN PENDEKATAN ARSITEKTUR PERILAKU - Rizki Ramadhan; Karya Widyawati; Wiyoga Triharto (Lakar: Jurnal Arsitektur, 2020)
The purpose design of flats at the Pondok Kelapa, east Jakarta, is to design a habitable, comfortable flat set aside for a people who live in a river side plan to be relocated by the government. With the construction of his unit's design for optimum lighting and air circulation, the apartment is not only comfortable but healthy. There are also support facilities and means for people living in the area Flat Pondok Kelapa of east Jakarta. The design uses the Behavioral Architecture Approach Concept, and uses the behavior mapping methodology, with the process of collecting data on an object and observing the object as data to be implemented to design an apartment in Pondok Kelapa, East Jakarta.